Preoperative Creatinine Clearance and Mortality of Elective Cardiac Surgery in Hospitalization: A Secondary Analysis - Chen, Lu; He, Yan; Song, Kai; Zhang, Bingqian; Liu, Lin (Frontiers in Cardiovascular Medicine, 2022)
Objective: It has been reported that poor renal function before surgery is related to poor prognosis. However, there is no specific discussion on the ideal value of preoperative creatinine clearance. Consequently, our primary goal is to explore the correlation between baseline creatinine clearance and short-term mortality after cardiac surgery. Methods: We conducted a secondary data analysis based on a French cardiac surgery cohort. The cohort included 6889 participants in a Paris university hospital from December 2005 to December 2012. The exposure variable and outcome variable used in this secondary analysis were the preoperative creatinine clearance rate and postoperative hospital mortality. Multivariate logistic regression and generalized additive models were employed. Results: The nonlinear relationship between the preoperative creatinine clearance rate and postoperative death was observed in this study. The preoperative creatinine clearance rate was negatively correlated with postoperative mortality in the range of 8.9 to 78.5 in patients younger than 80 years old (odds ratio = 0.98, 95% confidence interval 0.97 to 0.98, in Cockcroft Gault formulae). However, this effect characteristics reaches saturation after the preoperative creatinine clearance rate exceeds 78.5 (odds ratio = 0.99, 95% confidence interval 0.98 to 1.00, CG). In patients with history of thromboembolic event and coronary artery disease, the saturation effect were 30.8 mL.min-1 (CG) and 56.6 mL.min-1(CG) . Conclusion: In the range of 8.9–78.5 (Cockcroft), an increase in preoperative creatinine clearance is associated with a decrease in postoperative mortality with patients younger than 80 years old. In patients with a history of embolism and coronary artery disease, the cut-off points of the reduction in preoperative creatinine clearance associated with a in crease in postoperative mortality are 30.8 mL.min-1 and 56.6 mL.min-1.